Assessment Of Fetal Outcome In Women Undergoing Emergency Caesarean Section For Fetal Distress In Tertiary Care Hospital - Fatima, Noor; Iqbal, Khansa; Amna Abbasi; Waheed, Nabeela; Arooj, Amara; Sadaf, Maliha (Journal of Rawalpindi Medical College, 2024)
Objective: This study aims to assess the fetal outcome in terms of early neonatal mortality among women undergoing emergency caesarean section for fetal distress. Methods: It is a Descriptive cross-sectional study involving 167 patients who were diagnosed with fetal distress and underwent emergency c-sections. The study was conducted at the Department of Obstetrics & Gynecology Unit-II, Holy Family Hospital, Rawalpindi from 24-09-2018 to 24-03-2019. Frequencies of fetal death were evaluated. Effect modifiers were controlled by the stratification. A P-value of ≤ 0.05 was considered as significant. Results: The mean maternal age of the study population was found to be 24.59±3.20 years while the mean gestational age was recorded as 38.88±1.40 weeks. Fetal death was observed in 6.6% (n=11) of the total study population. A statistically significant difference was present among APGAR score, gestational age and fetal weight. However, statistically no significant difference was observed among maternal age, maternal height and maternal weight. Conclusions: The frequency of fetal death following emergency caesarean section for fetal distress was found to be 6.6% (n=11). A statistically significant difference (P≤0.05) was present among APGAR score, gestational age and fetal weight for fetal outcome in our study.